The Analysis of Factors Affecting Foreign Investment in Indonesia VECM Approach - Basuki, Agus Tri; Rudiana, Melda Nurfadilah (Universitas Islam Tribakti Lirboyo Kediri, 2024)
Investment has an important role in the economic development of a country through a funding vacuum, with investment inequality between regions can be overcome. This study aims to analyze the effect of exchange rates, inflation, interest rates and exports on Foreign Direct Investment (FDI) using the VECM approach. VECM is used in this analysis because it can be used to estimate short-term effects between variables and long-term effects from time series data. This model was chosen because the influence of exchange rates, inflation, interest rates and exports cannot occur directly, but takes time to affect changes in foreign investment in Indonesia. This study used data from 1992-2022 taken from the Central Statistics Agency report. The results show that exchange rates and exports in the short and long term have a significant influence on Foreign Investment in Indonesia. While inflation and interest rates in the short term do not show a significant influence on Foreign Investment in Indonesia, while inflation and interest rate variables in the long term show a positive and significant influence on Foreign Investment in Indonesia. To increase foreign investment in Indonesia, the central government together with local governments should strive for ease of business licensing and the provision of fiscal and non-fiscal incentives to investors who invest in priority sectors in encouraging increased employment.